2004
DOI: 10.1002/jmr.661
|View full text |Cite
|
Sign up to set email alerts
|

A new method for the screening of solid‐phase combinatorial libraries for affinity chromatography

Abstract: A new methodology for the rapid assessment of affinity ligands synthesized by combinatorial solid-phase chemistry is reported. This screening strategy utilizes the target protein conjugated to FITC, and represents an almost universal technique for the preliminary screening of solid-phase combinatorial libraries. The assessment of a triazine-scaffolded solid-phase combinatorial library of ligands, designed to bind to human IgG, was performed with FITC-human IgG, and the results compared with those obtained by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…It was formerly reported that the FITC-based screening methodology utilized as a first rapid assessment of the 136-membered random library, tends to give false positives but not false negatives (Roque et al, 2004). Therefore, most of the ligands showing negative results by this method were not included in a following screening step by affinity chromatography ( Second-generation ligand library: dual screening for cutinase binding and biological activity retention…”
Section: Screening Of a Random Combinatorial Library With Fitc-cutinasementioning
confidence: 99%
See 1 more Smart Citation
“…It was formerly reported that the FITC-based screening methodology utilized as a first rapid assessment of the 136-membered random library, tends to give false positives but not false negatives (Roque et al, 2004). Therefore, most of the ligands showing negative results by this method were not included in a following screening step by affinity chromatography ( Second-generation ligand library: dual screening for cutinase binding and biological activity retention…”
Section: Screening Of a Random Combinatorial Library With Fitc-cutinasementioning
confidence: 99%
“…The labelled protein was purified from the unconjugated fluorescein by gel filtration using a Sephadex G-25M column. The screening of the random combinatorial library was performed using the method described by Roque and co-workers (Roque et al, 2004) with the conjugate FITC-cutinase in equilibration buffer (20 mM Tris-HCl, pH 8.0). Imaging of the agarose beads was performed under a fluorescence microscope.…”
Section: Screening Of a Random Ligand Library With Fitc-cutinasementioning
confidence: 99%
“…These are: (a) reduced production costs (protein A chromatography alone can account for more than 35% of the downstream processing costs), (b) resistance to chemical and biological degradation, (c) resistance to harsh sanitation or sterilization conditions imposed by GMP protocols, and (d) they are readily amenable to scale up procedures. To address some of these issues, several researchers over the years have attempted to develop biomimetic ligands that have specific binding to immunoglobulins and can potentially replace protein A (Li et al, 1998;Teng et al, 1999;Labrou, 2003;Roque et al, 2004b;Ghose et al, 2006;.…”
Section: Introductionmentioning
confidence: 99%
“…The purity of the conjugate, FITC-labeled rPv, was confirmed by SDS-PAGE and Coomassie Blue staining, and its F/P ratio (F/P ratio is defined as the ratio of moles of FITC to moles of protein in the conjugate) was calculated by the equation F/P ϭ (2.77 ϫ A 495 )/(A 280 Ϫ(0.35 ϫ A 495 )) from the absorbance readings of the conjugated samples (42). To assess if rPv activity is affected by labeling with FITC, colony-forming unit assay was conducted to compare the growth inhibition rates of E. coli by FITC-labeled rPv and nonlabeled rPv.…”
mentioning
confidence: 99%